2018
DOI: 10.18009/jcer.466740
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Physical Education Pre-Service Teachers’ Leisure Boredom, Life Satisfaction and Social Connectedness

Abstract: The purpose of this study was to analyze perceived levels of leisure boredom, life satisfaction and social connectedness of pre-service physical education teachers according to some demographic variables, and to determine the relationship between leisure boredom, life satisfaction and social connectedness. While there were no significant differences between leisure boredom, dissatisfaction and life satisfaction of the participants and grade level and participation physical activity regularly, there were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…In other words, the satisfaction mean scores of participants with regular income were higher than the mean scores of others. In the literature, the findings of Kara et al (2018) and Çakır (2019) did not overlap with the current results. Similarly, the main effect of income status on the sub-dimensions of the LSS was statistically significant.…”
Section: Discussionsupporting
confidence: 49%
“…In other words, the satisfaction mean scores of participants with regular income were higher than the mean scores of others. In the literature, the findings of Kara et al (2018) and Çakır (2019) did not overlap with the current results. Similarly, the main effect of income status on the sub-dimensions of the LSS was statistically significant.…”
Section: Discussionsupporting
confidence: 49%
“…According to the analysis results within the framework of Boredom Perception in Leisure Time significant results in favor of women were determined in the boredom sub-dimension and significant results in favor of those who participate in physical activity were determined in the participation in physical activity sub-dimension. In the related literature, there are studies in which gender differences were not observed (Kara, Gürbüz & Sarol, 2018a;Kara, Gürbüz, Küç ük-Kılıç & Öncü, 2018b) within the framework of boredom perception as well as many studies in which gender differences in favor of males were determined (Kara et al, 2014;Leung, 2007). In addition to the boredom perception in leisure time and gender relationships, the role of physical activity is especially emphasized in coping with boredom perception in the studies performed in recent years (Deal, 2005;Sommers & Vodanovich, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the research carried out by Kara et.al. (38), it was determined that there is no significant difference in boredom and dissatisfaction subscales in terms of participation in physical activity.…”
Section: Discussionmentioning
confidence: 99%